Sensing strategy development for identification of trace elements and myelodysplastic syndrome based on fluorescent doped carbon quantum dots - Cruz, Antônio Alvernes Carneiro (2022)
Carbon Quantum Dots (CQDs) have received enormous attention over the past few years due to their chemical, electronic and optical properties. In this work, a series of CQDs doped with N, P and S were synthesized and their optical and structural properties evaluated. The synthetic route selected was thermolysis and citric acid (CA), ethylenediamine, phosphoric acid and mercaptosuccinic acid acted as sources of C, N, P and S, respectively. In addition, urea was used as a source of N for the synthesis of multicolored CQDs. The samples were structurally characterized and the results showed that the CQDs obtained had diameters in the range of 1-4 nm and present the previously chosen functional groups, in addition to disordered carbon. Subsequently, a “nose” approach was developed using a set of four distinct CQDs - Doped-ConBr (Doped = N, P and S), which allowed us to acquire different and reproducible fluorescence patterns for three carbohydrates (glucose, mannose and Methyl-α-D-mannopyroside) in a concentration range between 30-800 mol L-1. Subsequently, pattern recognition was performed using linear discriminant analysis (LDA) and 36 samples were correctly identified, with 100% accuracy. Then, a multichannel sensor was developed with a mixture of two CQDs for the identification of metal ions (Co2+, Cu2+, Mg2+, Mn2+, Fe2+, Mo2+, Zn2+) in the concentration range of 100-700 mol L-1. The results obtained were treated by principal component analysis (PCA) followed by LDA. In addition, another “nose” approach was developed using a set of three distinct CQDs - Doped-ConBr (Doped = P and S), which allowed us to acquire different and reproducible fluorescence patterns for peripheral blood and bone marrow samples. of patients affected by myelodysplastic syndrome (MDS).